Peer assessment using comparative and absolute judgement. (December 2015) - Jones, Ian; Wheadon, Chris
Highlights: School students assessed one another's work without assessment criteria. A comparative judgement approach yielded sound reliability and validity. An absolute judgement approach lacked reliability and validity. Peer assessment without criteria may be preferable in certain contexts. Abstract: Peer assessment exercises yield varied reliability and validity. To maximise reliability and validity, the literature recommends adopting various design principles including the use of explicit assessment criteria. Counter to this literature, we report a peer assessment exercise in which criteria were deliberately avoided yet acceptable reliability and validity were achieved. Based on this finding, we make two arguments. First, the comparative judgement approach adopted can be applied successfully in different contexts, including higher education and secondary school. Second, the success was due to this approach; an alternative technique based on absolute judgement yielded poor reliability and validity. We conclude that sound outcomes are achievable without assessment criteria, but success depends on how the peer assessment activity is designed.